Zone 5 une controverse en paysage - Hélène Gallezot (Projets de Paysage)
In the next few years, which will seemingly be marked by profound socio-demographic, functional and morphological mutations, suburbs of individual housing will surely have to be requalified. In this general context, the thesis which we here wish to examine, focuses on ordinary territories and how they are being appropriated day-by-day. The aim is to identify the mechanisms allowing the inhabitants of these territories to reveal the landscape qualities of their environment so that the landscape can be acknowledged by the different producers of the territory. We will highlight the process of landscape production. It is amidst confrontation and controversy that inhabitants of a particular territory pinpoint an esthetical value (an “esthetic of the ordinary”) on their daily environment.